Penerapan Pembelajaran CLIS dengan Menggunakan Alat Peraga Sederhana Untuk Meningkatkan Keterampilan Berpikir Pemecahan Masalah - Faradita, Meirza Nanda (IAIN Ponorogo, 2018)
ABSTRACT This study aims to improve thinking skills in solving problems of science subjects in fifth grade students at Tawangsari Elementary School. This study uses Classroom Action Research. The research subjects in this study were all students of V Tawangsari Taman-Sidoarjo class. With a total of 46 students, consisting of 25 men and 21 women. This class action research will be conducted at Tawangsari Elementary School Taman-Sidoarjo. In the first cycle, the average thinking problem solving skills of students is 68.47. The average value for the Daily Evaluation process (LKS) is 80.67 with very good criteria, and for Daily Evaluation the product (evaluation) is 68.02 with sufficient criteria. In the second cycle, the average value of students' problem solving thinking skills was 76.8. The average value for the process Daily Evaluation (LKS) and product (evaluation) is 94.35 and 76.49. Thus, it can be concluded that the response of students in learning science by applying CLIS learning by using simple teaching aids can improve thinking skills of problem solving and improve the completeness of student learning outcomes both in process and product. Keywords: CLIS Learning, Simple Props, Problem Solving Thinking Skills